Something other than God : how I passionately sought happiness and accidentally found it - Fulwiler, Jennifer (San Francisco Ignatius press, 2014)
Jennifer Fulwiler told herself she was happy. Why wouldn't she be? She made good money as a programmer at a hot tech start-up, had just married a guy with a stack of Ivy League degrees, and lived in a twenty-first-floor condo where she could sip sauvignon blanc while watching the sun set behind the hills of Austin. Raised in a happy, atheist home, Jennifer had the freedom to think for herself and play by her own rules. Yet a creeping darkness followed her all of her life. Finally, one winter night, it drove her to the edge of her balcony, making her ask once and for all why anything mattered. At that moment everything she knew and believed was shattered. Asking the unflinching questions about life and death, good and evil, led Jennifer to Christianity, the religion she had reviled since she was an awkward, skeptical child growing up in the Bible Belt. Mortified by this turn of events, she hid her quest from everyone except her husband, concealing religious books in opaque bags as if they were porn and locking herself in public bathroom stalls to read the Bible. Just when Jennifer had a profound epiphany that gave her the courage to convert, she was diagnosed with a life-threatening medical condition--and the only treatment was directly at odds with the doctrines of her new-found faith. Something Other Than God is a poignant, profound and often funny tale of one woman who set out to find the meaning of life and discovered that true happiness sometimes requires losing it all.
Keywords: Fulwiler, Jennifer; Catholic converts -- United States -- Biography; Authors, American -- Biography